The Unity of Judicial Practice - a Need and Desire of the Law Enforcement Process - I. L. Sitnikova (Сибирское юридическое обозрение, 2019)
The article examines the functioning of the judicial system of the Russian Federation, based on the delimitation of competence and the definition of the procedural relationship between the courts of different branches of jurisdiction. The Author considers the contradictions encountered in the decisions of the Constitutional Court and the Supreme Court, and the conflicts that exist in the decisions of the highest body of constitutional justice on the same subject matter. The proposed mechanisms for resolving conflicts in judicial practice are analyzed, relevant proposals are made to improve the current Russian legislation.